An observation and analysis of oboe works written by east Asian composers after 1945: featuring compositions by Isang Yun, Toshi Ichiyanagi, Makoto Shinohara, and Du Yun - Vollmuth, Briele Elizabeth (Kansas State University, 2023)
Through research and analysis, this document will uncover reactions to globalization in music within Eastern and Western music practice. Among the topics researched will be an exposition of Eastern and Western approaches to wind writing through an elaboration on historical and musical traditions of each practice. Chapters 1 and 2 of this document serves primarily to give historical context to the music analysis presented in Chapters 3 through 6. Since the works that are to be analyzed use or imitate non-Western techniques, I felt it necessary to preface the analysis with two informative chapters; one on relevant Western concepts and the other on relevant Eastern concepts. I felt this would give the reader a better understanding of what these composers were trying to achieve in addition to providing a clearer understanding of the music. Chapter 1 will focus on developments in Western music history, primarily the idea of exoticism, and how it influenced 20th-century composers. Furthermore, Chapter 1 will also uncover how the effects of the Great War and World War II made eastern music and instruments more accessible to composers. Chapter 2 will provide an overview of Western and Eastern music characteristics, primarily looking at the difference between Eastern and Western concepts. This will be followed by extensive research into the techniques of composers Isang Yun, Toshi Ichiyanagi, Makoto Shinohara, and Du Yun, highlighting their masterful juxtaposition of both practices in their own musical compositions. Furthermore, this research will survey the structural and theoretical analysis of the oboe composition Piri for solo oboe, Cloud Figures for solo oboe, Obsession for oboe and piano, and Angel’s Bone for oboe and tam tam by comparing their musical elements in combining aspects of both traditions. This information will be provided in Chapters 4 through 6, each opening with biographical information about the composer, followed by the analysis of their specified oboe work.
Keywords: Isang Yun; Toshi Ichiyanagi; Makoto Shinohara; Du Yun